2003
DOI: 10.1309/08j6mdlcjpphjnd1
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability in Assessing Adequacy of the Squamous Component in Conventional Cervicovaginal Smears

Abstract: We compared the interobserver reproducibility of estimating the adequacy of the squamous component of conventional Papanicolaou (Pap) smears using traditional and newly proposed criteria. Forty conventional Pap smears with varying degrees of squamous cellularity were reviewed by 13 observers who evaluated adequacy (satisfactory vs unsatisfactory) based on the traditional criterion of estimating 10% slide coverage. After being introduced to the new criterion and the reference images, the observers reevaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…They also reported that the proportion of smears designated as unsatisfactory based on the new guidelines was higher than that obtained using the 10% rule. 4 The mean proportion of smears designated as unsatisfactory was 0.34 using the 10% rule but was 0.51 using the new criterion. In the present study, we again demonstrated differences in the proportion of smears designated as inadequate based on the 2 criteria, with the Bethesda 2001 criterion proving to be a more strict assessment of adequacy, ie, more smears were classified as unsatisfactory because of inadequate squamous cellularity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…They also reported that the proportion of smears designated as unsatisfactory based on the new guidelines was higher than that obtained using the 10% rule. 4 The mean proportion of smears designated as unsatisfactory was 0.34 using the 10% rule but was 0.51 using the new criterion. In the present study, we again demonstrated differences in the proportion of smears designated as inadequate based on the 2 criteria, with the Bethesda 2001 criterion proving to be a more strict assessment of adequacy, ie, more smears were classified as unsatisfactory because of inadequate squamous cellularity.…”
Section: Discussionmentioning
confidence: 89%
“…Most investigators agreed that interobserver reproducibility in assessing squamous adequacy using the 10% rule ranged from poor to fair. 4,9,11 In view of the limitations and controversies associated with the 10% rule, Bethesda 2001 proposed a new criterion for adequate squamous cellularity for conventional smears-a conventional Pap smear should have an estimated minimum of approximately 8,000 to 12,000 well-preserved and well-visualized squamous epithelial cells. 3 Computer-generated images of known cellular density are used as references to compare with smears to assess adequacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 This is especially important in resourcelimited settings, such as South Africa, where a woman may undergo screening only once in her lifetime. 29,30 Conventionally, a cervical smear is considered to be satisfactory for evaluation if it has an estimated minimum of 8 000-12 000 clearly displayed squamous epithelial cells. 29,30 The Limpopo province recorded high smear adequacy rates throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Conventionally, a cervical smear is considered to be satisfactory for evaluation if it has an estimated minimum of 8 000-12 000 clearly displayed squamous epithelial cells. 29,30 The Limpopo province recorded high smear adequacy rates throughout the study period.…”
Section: Discussionmentioning
confidence: 99%